Methodological procedures for sustainable fashion design in academic environment (ModaPalavra e-periódico, 2016)
Recent studies have shown that the role of the designer in a fashion company can be decisive in the development of more sustainable products. Typically, the designer is the most committed professional with the sustainable cause and possessing knowledge of the entire production chain, being able to perceive in every life cycle phase the opportunities to bring changes. From this perspective, this article presents the results of teaching and learning experiences in the fashion graduation course. The qualitative research used data collection fromliterature review, tacit knowledge of fashion companies and participant observation of teaching practices in the classroom. The objective is to share results and propose a discussion between pairs of a set of methodological procedures of design for sustainability, seeking aid awareness and training future fashion designers.
Keywords: higher education; fashion design; sustainability